Bilans energetyczny budynku - Przetocki, Marek (Zielona Góra: Uniwersytet Zielonogórski)
A test of join of warmth losses with environement are taken on. All problems related with this issue and the possibility of reduction of energetic losses in buildings are described. Also the review of Polish and foreign methods are presented.
Keywords: budownictwo; bilans energetyczny